2015
DOI: 10.1242/jcs.170316
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite arborization requires the dynein cofactor NudE

Abstract: The microtubule-based molecular motor dynein is essential for proper neuronal morphogenesis. Dynein activity is regulated by cofactors, and the role(s) of these cofactors in shaping neuronal structure are still being elucidated. Using Drosophila melanogaster, we reveal that the loss of the dynein cofactor NudE results in abnormal dendrite arborization. Our data show that NudE associates with Golgi outposts, which mediate dendrite branching, suggesting that NudE normally influences dendrite patterning by regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 62 publications
7
70
0
1
Order By: Relevance
“…As CDK5 activity acts through Ndel1 and Lis1 to regulate dynein motor function (Figure 3C), we hypothesize that the observed effects of CDK5 disruption are due to dysregulation of dynein activation in the AIS. These results confirm previous observations in Drosophila wherein inhibition of dynein or NudE disrupted axonal microtubule polarity, 18,43 but extend these findings by demonstrating the upstream regulatory pathway involved. We next sought to determine if other known functions of dynein in the AIS are affected by CDK5 inhibition.…”
Section: Resultssupporting
confidence: 92%
“…As CDK5 activity acts through Ndel1 and Lis1 to regulate dynein motor function (Figure 3C), we hypothesize that the observed effects of CDK5 disruption are due to dysregulation of dynein activation in the AIS. These results confirm previous observations in Drosophila wherein inhibition of dynein or NudE disrupted axonal microtubule polarity, 18,43 but extend these findings by demonstrating the upstream regulatory pathway involved. We next sought to determine if other known functions of dynein in the AIS are affected by CDK5 inhibition.…”
Section: Resultssupporting
confidence: 92%
“…However, in apparent contradiction with this possibility, gradual depletion of dynein heavy chain (DHC) from cultured rat neurons from the superior cervical ganglion (SCG) resulted in diminution of the anterograde but not retrograde transport of axonal MTs (He et al, 2005). This may be because gradual depletion of DHC provides the opportunity for other motors to aberrantly transport MTs (Baas and Mozgova, 2012, Arthur et al, 2015, Zheng et al, 2008). Here we used various methods including an acute approach to test dynein’s potential role in polarity sorting axonal MTs, and then used computational modeling to ascertain whether the data can be explained by dynein-based polarity sorting of MTs.…”
Section: Introductionmentioning
confidence: 99%
“…If Golgi outposts are capable of regulating microtubule organization, we reasoned that their ectopic presence in axons should disrupt the uniform plus-ends-distal array of axonal microtubules. To ectopically localize Golgi outposts to axons, we relied on mutations that disrupt the activity of the molecular motors dynein and kinesin-1, which transport outposts (Arthur et al, 2015;Kelliher et al, 2019;Lin et al, 2015;Ye et al, 2007;Zheng et al, 2008). While disrupting the activity of either motor results in Golgi outposts invading axons, we and others have previously shown that these ectopic outposts do not always correlate with a change in axonal microtubule polarity (Kelliher et al, 2019;Nguyen et al, 2014;Ye et al, 2007).…”
Section: Loss Of Gm130 Significantly Reduces Misoriented Microtubulesmentioning
confidence: 99%
“…The loss of dynein activity alters both Golgi outpost localization and axonal microtubule polarity (Arthur et al, 2015;del Castillo et al, 2015;Klinman et al, 2017;Rao et al, 2017;Zheng et al, 2008). We first asked whether the misoriented microtubules in dynein loss-of-function neurons depend on the ectopic Golgi outposts.…”
Section: Loss Of Gm130 Significantly Reduces Misoriented Microtubulesmentioning
confidence: 99%
See 1 more Smart Citation